When to replace legacy cochlear implants for technological upgrades: Indications and outcomes. (28th November 2018) - Holcomb, Meredith A.; Burton, Jane A.; Dornhoffer, James R.; Camposeo, Elizabeth L.; Meyer, Ted A.; McRackan, Theodore R.
Abstract : Objective: To determine indications, surgical efficacy, and audiologic outcomes of replacing Advanced Bionics Clarion C1.2 internal devices (Advanced Bionics, LLC, Valencia, CA) as a means of technology upgrade. Study Design: Retrospective review, case series. Methods: Ten patients were initially implanted as a child (mean age = 3.87 years) and underwent cochlear implant reimplantation (CIR) with current Advanced Bionics internal device as a young adult (mean duration of implant use = 15.66 years). Demographic data and pre‐ and post‐CIR speech perception scores were collected. Results: Technology upgrade was the primary (9) or secondary (1) motivation for CIR. No surgical complications were noted, and full insertion was obtained in nine cases. Intraoperative impedance levels and neural response imaging measures were within normal limits for eight patients. At most recent post‐CIR follow‐up evaluation, all patients (100%) performed within or better than the 95% confidence interval of their pre‐CIR word and sentence recognition scores; and 55.6%, 50.0%, and 50.0% of patients performed above the 95% confidence interval of their pre‐CIR scores for the CNC words, sentences in quiet, and sentences in noise, respectively. Conclusion: Post‐CIR audiological benefit was stable or improved compared to pre‐CIR results in all categories by 3 months after reactivation. Given these results, patients who are unable to use the most current external processors due to incompatibility with a legacy internal device could consider reimplanation to optimize their overall performance with a cochlear implant. Level of Evidence: 4 Laryngoscope, 129:748–753, 2019